FUNGSI MANAJEMEN KOORDINATOR KIA DALAM PENCAPAIAN CAKUPAN ASI EKSKLUSIF DI KOTA PALANGKA RAYA - Nuryanti Nuryanti; Andarini Indreswari; Eti Rimawati (Dian Nuswantoro Semarang, 2011)
Background: The management function application is a main concern to decrease the number of infant mortality. Based on health profile of Palangka Raya in 2008, the coverage of exclusive breastfeeding was less than 50% than 80% (target of coverage). The purpose of thisresearch is to examine the relation between management function of safe motherhood coordinators with the coverage of exclusive breastfeeding in Palangka Raya.Method: This research is an explanatory research, by using survey method and cross sectional approach. The sample of the research was the total population of safe motherhoodcoordinators (9 respondents). The analyzing of data was rank Kendall’s correlation test.Result: The rank Kendall’s correlation test shows that there is a relation among planning function (p-value 0.008), direction function (p-value 0.009), coordinating function (p-value 0.029) and evaluation function (p-value 0.032) with exclusive breastfeeding.Key words: exclusive breastfeeding coverage, management functions